Technology acceptance and students’ attitude towards technology-based self-directed learning: The mediation effect of technological self-efficacy and learning motivation - Boniface Aabeyir; Francis Ohene Boateng (Universitas Sarjanawiyata Tamansiswa, 2025)
The study investigated how students at three public colleges of education in the Ashanti Region perceive and engage with technology-driven self-directed learning. Specifically, it examined the interconnections among technology acceptance, technological self-efficacy, learning motivation, and attitudes towards technology-based self-directed learning. The study also investigated the mediating role of technological self-efficacy between technology acceptance and learning motivation, as well as the mediating role of learning motivation between technological self-efficacy and attitudes towards technology-based self-directed learning. Additionally, it explored the combined mediation effect of both technological self-efficacy and learning motivation on the relationship between technology acceptance and attitudes towards technology-based self-directed learning in mathematics. Using structural equation modeling (SEM) with 237 purposefully selected participants, the findings revealed several insights. First, there was no significant direct relationship between technology acceptance and attitudes towards technology-based self-directed learning. Second, technological self-efficacy did not significantly influence attitudes towards technology-based self-directed learning independently. However, learning motivation was found to significantly impact students' attitudes towards technology-based self-directed learning. Furthermore, the study indicated that technological self-efficacy partially mediated the relationship between technology acceptance and learning motivation. Crucially, both technological self-efficacy and learning motivation together significantly mediated the relationship between technology acceptance and attitudes towards technology-based self-directed learning. Based on these findings, the study recommended that educators guide students by providing access to user-friendly and beneficial technological tools. This approach aims to inspire and motivate students to effectively participate in independent learning using technology.